Comparison of Standard and Intensified Regimens for HIV-Negative Adults With Tuberculous Meningitis in West China: A Retrospective Observational Study - Abdulaziz, Ammar Taha Abdullah; Ren, Yi Meng; Li, Wei; Li, Jin Mei; Zhou, Dong (Frontiers in Neurology, 2019)
Background: Tuberculous meningitis (TBM) is an extremely devastating inflammation of the central nervous system; however, no available optimum treatment can effectively control the disease so far. Method: The medical records of TBM patients from May 2011 to August 2016 in West China hospital were retrospectively analyzed. Patients were divided into three groups based on their treatment regimens {Group1: 4 standard therapy; Group2: 3 standard drugs + Levofloxacin; Group3: 4 standard therapy + Levofloxacin (G3a)/ Moxifloxacin (G3b)}. Using the intention-to-treat analysis, eventually, the treatments' efficacy and safety were compared among all groups. Results: Two hundred two patients with TBM were enrolled and followed up for at least 2 years. Among them, 99 patients were in G1; 18 in G2; and 85 in G3 (Moxifloxacin=39/ Levofloxacin=49). One hundred fifteen (56.9%) patients were males, and the median age was 42 years. At admission, 74 patients (36.6%) were in stage I, 102 (50.5%) in stage II and 26 (12.9%) in stage III. The most common symptoms were headache in 194 (96.0%) patients, fever in 162 (80.2%), vomiting in 120 (59.7%), neck stiffness in 104 (51.5%), and malaise in 96 (47.5%). The overall outcome at 1 year showed that 47 patients (47.5%) in G1, 10 patients (55.6%) in G2 and 48 patients (56.5%) in G3 had good outcome; however, there was no significant difference among all groups (P = 0.397); at 2 years there was also no difference among treatment groups (P = 0.295). However, in Group3b 22 patients (56.4%) at 1-year and 26 (66.7%) at 2-year follow up had a full recovery, which is significantly superior to other treatment groups, the P value at 1 and 2 years was 0.002 and 0.027, respectively. Conclusion: The overall outcome in patients with TBM at 1 and 2 years follow up did not show any statistically significant difference between the standard chemotherapy and other intensified regimens. Furthermore, Hydrocephalus (OR = 3.461, 95% CI: 1.349–8.882, P = 0.010) was the only independent risk factor for a poor outcome.